Age as a risk factor for acute mountain sickness upon rapid ascent to 3,700 m among young adult Chinese men - Tang XG (Dove Medical Press, 2014)
Xu-gang Tang,1 Ji-hang Zhang,1 Jun Qin,1 Xu-bin Gao,1 Qian-ning Li,2 Jie Yu,1 Xiao-han Ding,1 Lan Huang1 1Institute of Cardiovascular Diseases, 2Department of Neurology, Xinqiao Hospital, Third Military Medical University, Chongqing, People’s Republic of China Background: The aim of this study was to explore the relationship between age and acute mountain sickness (AMS) when subjects are exposed suddenly to high altitude.Methods: A total of 856 young adult men were recruited. Before and after acute altitude exposure, the Athens Insomnia Scale score (AISS) was used to evaluate the subjective sleep quality of subjects. AMS was assessed using the Lake Louise scoring system. Heart rate (HR) and arterial oxygen saturation (SaO2) were measured.Results: Results showed that, at 500 m, AISS and insomnia prevalence were higher in older individuals. After acute exposure to altitude, the HR, AISS, and insomnia prevalence increased sharply, and the increase in older individuals was more marked. The opposite trend was observed for SaO2. At 3,700 m, the prevalence of AMS increased with age, as did severe AMS, and AMS symptoms (except gastrointestinal symptoms). Multivariate logistic regression analysis showed that age was a risk factor for AMS (adjusted odds ratio [OR] 1.07, 95% confidence interval [CI] 1.01–1.13, P<0.05), as well as AISS (adjusted OR 1.39, 95% CI 1.28–1.51, P<0.001).Conclusion: The present study is the first to demonstrate that older age is an independent risk factor for AMS upon rapid ascent to high altitude among young adult Chinese men, and pre-existing poor subjective sleep quality may be a contributor to increased AMS prevalence in older subjects. Keywords: acute mountain sickness, age, Athens Insomnia Scale, rapid ascent, sleep